Habitat use of barbel (Barbus barbus) in a restored urban Danube tributary - Popp, Stephanie; Pinter, Kurt; Schwayer, Christoph; Hayes, Daniel S. (Frontiers in Environmental Science, 2024)
Tributaries play a vital role in fish spawning and recruitment, significantly influencing mainstem river fish populations. However, in the Anthropocene era, tributaries within river networks suffered ecological degradation due to fragmentation and channelization. This has led to reduced distribution ranges and declining populations of various riverine species, underscoring the urgency of conservation and rehabilitation efforts. Our study explores the potential for reintroducing fish from the mainstem Danube River into the Wien River, an urban tributary that has undergone partial rehabilitation. We assessed habitat use and movement patterns of 20 adult barbel (Barbus barbus), a species classified as ‘near threatened’ in Austria, collected from the Danube River during the spawning season. These barbel were tagged with radio telemetry tags and relocated into the upper reaches of the Wien River, surmounting several artificial barriers in the lower sections. Although spawning activity was not observed among the barbel, possibly due to prevailing water temperatures, our data suggest that the Wien River could function as a viable temporary habitat. Barbel were notably inclined to inhabit deeper pool and run habitats. Their daily movements and home ranges were relatively limited, ranging from 0.0 to 1.1 km and 100 m to 2.9 km, respectively. One contributing factor to restricted movement was the presence of beaver and knotweed dams, which created temporary migration obstacles. On average, the barbel remained within the system for more than a month. Most of these fish migrated downstream at the onset of a significant high-flow event. Our assessment suggests that while the Wien River may not serve as a permanent habitat, it could function as a temporary habitat for migratory fish. However, to ensure accurate assessments of the restored Wien River as a spawning habitat, it is imperative to reevaluate the findings under stable spawning conditions and gather comprehensive data on relevant abiotic factors. This study advocates for the restoration of longitudinal connectivity between tributaries and mainstem rivers as a means to counteract biodiversity loss in Anthropocene river ecosystems.